Mephistopheles and Inflation - Karl Brunner (Kredit und Kapital, 1990)
Mephistopheles and Inflation Karl Brunner died on May 9, 1989 in Rochester, New York. Prof. Michele Fratianni of Indiana University, while researching Brunner's academic life, found the unpublished paper "Mephistopheles and Inflation" which he submitted to Kredit und Kapital. The paper deals with one of Brunner's favorite research themes: money, inflation, and public choice. The structure of the paper goes as follows. Inflation is mostly a monetary phenomenon. Money is power. The Faustian Mephisto all too well understood this power when he proposed that the Emporer back his paper money by the unknown and buried treasures of the empire. Modern democracies have improved on the Mephisto's scheme only technologically. Politicians resort to inflation because it embeds a lower cost than either cutting expenditures or raising tax rates. Permanent inflation reflects a pervasive political crisis of modern societies and pushes us closer to Leviathan.
Keywords: 330